Sustainability logos and claims on food packaging and labels: The case of Türkiye - Nesli Ersoy; Bensu Budak (PLoS ONE, 2025)
Enhancing consumer awareness of sustainable nutrition is a key factor in promoting public health and supporting environmentally friendly food systems. Logos and claims on food packaging that indicate the use of sustainable production methods have the potential to increase awareness, improve accessibility, and encourage producers. This study represents the first systematic audit aimed at assessing the current situation in Türkiye concerning the use of sustainability-related labels and claims, while also providing scientific insights for producers. The presence of sustainability-related logos and claims was examined on food packages displayed in the shelves of one branch from each major grocery chain in a district of Türkiye’s Region 1. In total, 3,085 food products were assessed in three grocery stores. The analysis included logos and claims related to sustainability, such as animal welfare, organic production, recyclable packaging, the Green Dot (ÇEVKO), Rainforest Alliance certification, local production, geographical indication, good agricultural practices, and vegan/vegetarian declarations. All grocery stores provide recycling bins, and reusable shopping bags are strategically positioned in highly visible areas to encourage consumer use. It has been determined that the logo most frequently appearing on food packaging is the recycling logo (87.4%), while the least frequently appearing logos are the organic production logo (0.3%) and the animal welfare declaration (0.13%). The food categories displaying the greatest number of logos on their packaging, in order, were beverages, sugars (including candies), and meat, poultry, fish, and their products. There is a need to increase the number and visibility of sustainability-related logos and claims on food products. The food industry should be encouraged to adopt more environmentally sustainable practices, both in production and packaging.